Maternal caloric restriction partially rescues the deleterious effects of advanced maternal age on offspring. Issue 4 (24th March 2014) - Gribble, Kristin E.; Jarvis, George; Bock, Martha; Mark Welch, David B.
Summary While many studies have focused on the detrimental effects of advanced maternal age and harmful prenatal environments on progeny, little is known about the role of beneficial non‐Mendelian maternal inheritance on aging. Here, we report the effects of maternal age and maternal caloric restriction (CR) on the life span and health span of offspring for a clonal culture of the monogonont rotifer Brachionus manjavacas. Mothers on regimens of chronic CR (CCR) or intermittent fasting (IF) had increased life span compared with mothers fed ad libitum (AL). With increasing maternal age, life span and fecundity of female offspring of AL‐fed mothers decreased significantly and life span of male offspring was unchanged, whereas body size of both male and female offspring increased. Maternal CR partially rescued these effects, increasing the mean life span of AL‐fed female offspring but not male offspring and increasing the fecundity of AL‐fed female offspring compared with offspring of mothers of the same age. Both maternal CR regimens decreased male offspring body size, but only maternal IF decreased body size of female offspring, whereas maternal CCR caused a slight increase. Understanding the genetic and biochemical basis of these different maternal effects on aging may guide effective interventions to improve health span and life span.